Development and evaluation of an 18F-labeled nanobody to target SARS-CoV-2's spike protein - Lopes van den Broek, Sara; García-Vázquez, Rocío; Andersen, Ida Vang; Valenzuela-Nieto, Guillermo; Shalgunov, Vladimir; Battisti, Umberto M.; Schwefel, David; Modhiran, Naphak; Kramer, Vasko; Cheuquemilla, Yorka; Jara, Ronald; Salinas-Varas, Constanza; et al. (Frontiers in Nuclear Medicine, 2022)
COVID-19, caused by the SARS-CoV-2 virus, has become a global pandemic that is still present after more than two years. COVID-19 is mainly known as a respiratory disease that can cause long-term consequences referred to as long COVID. Molecular imaging of SARS-CoV-2 in COVID-19 patients would be a powerful tool for studying the pathological mechanisms and viral load in different organs, providing insights into the disease and the origin of long-term consequences and assessing the effectiveness of potential COVID-19 treatments. Current diagnostic methods used in the clinic do not allow direct imaging of SARS-CoV-2. In this work, a nanobody (NB) – a small, engineered protein derived from alpacas – and an Fc-fused NB which selectively target the SARS-CoV-2 Spike protein were developed as imaging agents for positron emission tomography (PET). We used the tetrazine ligation to 18F-label the NB under mild conditions once the NBs were successfully modified with trans-cyclooctenes (TCOs). We confirmed binding to the Spike protein by SDS-PAGE. Dynamic PET scans in rats showed excretion through the liver for both constructs. Future work will evaluate in vivo binding to the Spike protein with our radioligands.